Peristiwa Sejarah dalam Novel Cut Nyak Dien: sebuah Novel Epik Perang Aceh Karya Sayf Muhammad Isa - Nursari, Isfiana; Munira, Najimah; Isnaini, Wirdatul; Munawarah, Intan (Medan Resource Center, 2024)
This study aims to describe historical elements, specifically events, depicted in the novel Cut Nyak Dien: Sebuah Novel Epik Perang Aceh by Sayf Muhammad Isa. The primary data source for this research is the novel itself, spanning 791 pages and published by Qanita in 2015. The data analyzed consists of quotes, clauses, and sentences that serve as markers of historical events (what). This study employs a qualitative approach and utilizes descriptive research methods, with data collection conducted through documentation techniques. The results reveal a diverse range of historical events depicted in the novel, from Habib Abdurrahman Azzahir and Teuku Nyak Abbas seeking assistance from the Sharif of Mecca to the struggles of prominent figures such as Teungku Chik Tiro within the context of the Aceh War. The findings suggest that the novel embodies significant historical representations, enriching readers' understanding of the Acehnese resistance.